LIBERANDO ECOS: A METHODOLOGICAL, COUNTERHEGEMONIC, COLECTIVE AND PERFORMATIVE PROPOSAL FOR THE CONSTRUCTION OF A DIGNITY IN RESISTANCE - Orozco, Esteban Alfaro (2019)
The present document is the post-experiential theoretical-methodological revision of the Literary Arts Promotion Project at the Sandoval de Limón Penitentiary Center: Liberando Ecos (2016). This review aims to delimit methodologically and theoretically the contributions of the Circulo Literario Vertedero Satelite for the construction of dignities in resistance through a counter hegemonic, collective and performative conception of art.